The biocatalytic activity of the "lantern-like" binuclear copper complex with trisulfide bridges mimicking SOD metallo-proteins. (15th July 2022) - Caro-Ramirez, Janetsi Y.; Parente, Juliana E.; Gaddi, Gisela M.; Martini, Nancy; Franca, Carlos A.; Urquiza, Nora M.; Lezama, Luis; Piro, Oscar E.; Echeverría, Gustavo A.; Williams, Patricia A.M.; Ferrer, Evelina G.
Graphical abstract: Through a redox process, an in situ transformation of propylthiouracil led to the formation of a trisulfur ligand forming with Cu(II) a lantern-like binuclear complex [Cu2 (ptu-S-ptu)2 ]. The complex behaves as a promiscuous promising catalyst. It possesses peroxidase-like activity catalyzing phenol red bromination, the oxidation of pyrogallol, and behaves as a superoxide dismutase (SOD) mimic compound. Insights into their reactivity are analyzed by comparison with a family of other sulfur-containing copper(II) metal complexes. Abstract: Through a redox process, an in situ transformation of propylthiouracil led to the formation of a trisulfur ligand that coordinates Cu(II) ion forming a lantern-like binuclear copper(II) complex [Cu2 (ptu-S-ptu)2 ]. The complex was characterized by elemental analysis, spectroscopic techniques (FTIR, UV–Vis, EPR, and Hirshfeld surfaces analyses.), single-crystal X-Ray analysis, and its optimized molecular structure was obtained by DFT calculations. It crystallizes as a twin in the space group P -1, with two different, though closely related, centrosymmetric binuclear complexes per unit cell. The (ptu-S-ptu) 2− thiouracil rings are nearly perpendicular to each other and their N and O atoms equatorially cis -coordinate the two copper ions in a two-fold Cu-OCN-Cu bridging mode. The four-fold bridging configuration is completed by another (ptu-S-ptu) 2− ligand, inversion-related through the middle of the Cu…Cu contact. The elongated octahedral coordination around each copper is completed by the linking S-atom of the ligand at the axial position. The crystallographic results point to a copper d(x 2 -y 2 ) d -orbital for the electron (or hole) ground state and optimal overlap of this orbital with molecular electronic path bridging the two metal atoms, hence indicating a relatively large antiferromagnetic coupling between them. The designed complex behaves as a promiscuous promising catalyst. It possesses intrinsic peroxidase-like activity catalyzing phenol red bromination in the presence of H2 O2 at room temperature, and the oxidation of pyrogallol, and behaves as a superoxide dismutase (SOD) mimic compound acting on superoxide anion. Additionally, insights into their reactivity are analyzed by comparison with a family of other sulfur-containing copper(II) metal complexes in an attempt to explain the differences in catalytic properties and to determine the structural properties that affect the reactivity with substrates. Albumin interactions studies are also incorporated.